Absence of warmth permits epigenetic memory of winter in Arabidopsis - Jo Hepworth (Nature Portfolio, 2018)
Plants use multiple cues to monitor seasonal temperatures. Here, the authors show that Arabidopsis requires not only prolonged cold, but the absence of temperature spikes above 15 °C to epigenetically silence FLC during winter.